High Monocyte-To-Lymphocyte Ratio Is Associated With Stroke-Associated Pneumonia - Cheng, Hao-Ran; Song, Jia-Ying; Zhang, Yi-Nuo; Chen, Yun-Bin; Lin, Gang-Qiang; Huang, Gui-Qian; He, Jin-Cai; Wang, Zhen (Frontiers in Neurology, 2020)
Abstract Purpose: Stroke-associated pneumonia (SAP), a common complication in acute ischemic stroke (AIS) patients, is associated with poor prognosis after AIS. Inflammation plays an important role in the development of SAP. In this study, we aimed to explore the association between monocyte-to-lymphocyte ratio (MLR) and SAP in AIS patients. Methods: We continuously enrolled 972 AIS patients. SAP was diagnosed by two trained neurologist and was confirmed by radiography, meeting the modified Centers for Disease Control and Prevention criteria. MLR values were measured for all participants, and all patients were evenly classified into three tertiles according to the MLR levels. We used the values that Youden’s index max points corresponded to represent the optimal cut-offs, which represented the balance in sensitivity and specificity. Results: 104 (10.7%) patients were diagnosed with SAP. SAP patients showed a significant increased (P < 0.001) MLR when compared with non-SAP. The optimal cut-off points of MLR were: (T1) < 0.2513, (T2) 0.2513-0.3843, (T3) > 0.3843. The incidence of SAP was significantly higher in the third MLR tertile than the first and second MLR tertiles (21.7% versus 4% versus 6.5%, respectively, P < 0.001). After adjusting for confounding and risk factors, multivariate regression analysis showed that the third MLR tertile was an independent variable predicting the occurrence of SAP (OR = 3.503, 95%CI = 1.066-11.515, P = 0.039). Conclusions: Our study showed that higher MLR was significantly associated with SAP in AIS patients. MLR is beneficial for clinicians to recognize patients with high risk of SAP at early stage and is an effective way to improve clinical care of SAP patients. Higher MLR could be a helpful and valid biomarker for predicting SAP in clinical practice.